1986
DOI: 10.1177/088626086001001004
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Child Sexual Abuse

Abstract: A number of surveys have by now provided information about the relative risk of persons from various backgrounds to experience sexual abuse during childhood. Interestingly, they are fairly uniform in failing to find differences in rates according to social class or race. However, several other factors have emerged from community studies as being consistently associated with higher risk for abuse: (a) when a child lives without one of the biological parents; (b) when the mother is unavailable to the child eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 10 publications
2
74
0
2
Order By: Relevance
“…Surprisingly, one half to three quarters of victims reported that they had been molested by juveniles, and only 0% -10.7% of victims reported family members as perpetrators, depending on the type of CSA and the victim's gender. Consistent with previous literature [13,19,24]., predictors of CSA were being female, not living with both biological parents, and having parents with a lower education level or of non-Swiss nationality.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, one half to three quarters of victims reported that they had been molested by juveniles, and only 0% -10.7% of victims reported family members as perpetrators, depending on the type of CSA and the victim's gender. Consistent with previous literature [13,19,24]., predictors of CSA were being female, not living with both biological parents, and having parents with a lower education level or of non-Swiss nationality.…”
Section: Discussionsupporting
confidence: 87%
“…There is also evidence that, compared with men, women in the general population present with much higher rates of somatoform disorders in general (Kirmayer & Taillefer, 1997), experience more dissociation around the time of trauma (e.g., Cardeña & Spiegel, 1991;Koopman, Classen, & Spiegel, 1996), perceive some stressful events as more distressing (Caballo & Cardeña, 1997), and generally have a greater probability of developing PTSD after a traumatic event (e.g., Breslau & Davis, 1992). The greater incidence of somatoform disorders (including PNES), PTSD, and dissociation might be partly explained by the greater rate of sexual abuse of women than of men (Finkelhor & Barron, 1986;Stein, Walker, & Forde, 2000). Nonetheless, the possibility that hormonal and neurological differences between the genders (Springer & Deutsch, 1993) may help explain some of these difference should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Sexually abused mothers were also more likely to view their children as "a close friend or primary companion," and to depend upon their children for emotional support, again suggesting a pattern of role reversal (Burkett, 1991). Finkelhor and Baron (1986) have noted that failure on the part of survivors to maintain appropriate relationship boundaries with their own children could increase their children's vulnerability to abuse by a male partner, suggesting one potential mechanism for intergenerational transmission of CSA.…”
Section: Parentingmentioning
confidence: 98%